Normal Light-Dark and Short-Light Cycles Regulate Intestinal Inflammation, Circulating Short-chain Fatty Acids and Gut Microbiota in Period2 Gene Knockout Mice - Zhen, Yongkang; Ge, Ling; Xu, Qiaoyun; Hu, Liangyu; Wei, Wenjun; Huang, Jiantao; Loor, Juan J.; Yang, Qingyong; Wang, Mengzhi; Zhou, Ping (Frontiers in Immunology, 2022)
Regular environmental light-dark (LD) cycle-regulated period circadian clock 2 (Per2) gene expression is essential for circadian oscillation, nutrient metabolism and intestinal microbiota balance. Herein, we combined environmental LD cycles with Per2 gene knockout to investigate how LD cycles mediate Per2 expression to regulate colonic and cecal inflammatory and barrier functions, microbiome and short-chain fatty acid (SCFAs) in the circulation. Mice were divided into knockout (KO) and wild-type (CON) under normal light-dark cycle (NLD) and short-light (SL) cycle for 2 weeks after 4 weeks of adaptation. The concentrations of SCFAs in serum and large intestine, the colonic and cecal epithelial circadian rhythm, SCFAs transporter, inflammatory and barrier-related genes, and Illumina 16S rRNA sequencing were measured after euthanasia during 10:00-12:00. KO decreased the feeding frequency at 0:00-2:00, but increased at 12:00-14:00 both under NLD and SL. KO up-regulated the expression of Per1, Rev-erbα in colon and cecum, while down-regulated Clock and Bmal1. In terms of inflammatory and barrier functions, KO increased the expression of Tnf-α, Tlr2, and Nf-κb p65 in colon and cecum, while decreased Claudin and Occludin-1. KO decreased the concentrations of total SCFAs and acetate in colon and cecum, but increased butyrate, while it had no impact on SCFAs in serum. KO increased the SCFAs transporter because of the up-regulation of Nhe1, Nhe3, and Mct4. Sequencing data revealed that KO improved bacteria α-diversity, increased Lachnospiraceae and Ruminococcaceae abundance, while it down-regulated Erysipelatoclostridium, Prevotellaceae UCG_001, Olsenella, and Christensenellaceae R-7 under NLD in KO mice. Most of the differential bacterial genus were enriched in amino acid and carbohydrate metabolism pathways. Overall, Per2 knockout altered circadian oscillation in the large intestine, KO improved intestinal microbiota diversity, the increase of Clostridiales abundance led to reduction of SCFAs in the circulation, concentrations of total SCFAs and acetate decreased while butyrate increased and SCFAs transport was enhanced. These alterations may potentially have led to inflammation of the large intestine. Short-light treatment had minor impact on intestinal microbiome and metabolism.